Saharan dust and association between particulate matter and case-specific mortality: a case-crossover analysis in Madrid (Spain) - Díaz Julio; Tobías Aurelio; Linares Cristina (BMC, 2012)
Abstract Background Saharan dust intrusions are a common phenomenon in the Madrid atmosphere, leading induce exceedances of the 50 μg/m3- EU 24 h standard for PM10. Methods We investigated the effects of exposure to PM10 between January 2003 and December 2005 in Madrid (Spain) on daily case-specific mortality; changes of effects between Saharan and non-Saharan dust days were assessed using a time-stratified case-crossover design. Results Saharan dust affected 20% of days in the city of Madrid. Mean concentration of PM10 was higher during dust days (47.7 μg/m3) than non-dust days (31.4 μg/m3). The rise of mortality per 10 μg/m3 PM10 concentration were always largely for Saharan dust-days. When stratifying by season risks of PM10, at lag 1, during Saharan dust days were stronger for respiratory causes during cold season (IR% = 3.34% (95% CI: 0.36, 6.41) versus 2.87% (95% CI: 1.30, 4.47)) while for circulatory causes effects were stronger during warm season (IR% = 4.19% (95% CI: 1.34, 7.13) versus 2.65% (95% CI: 0.12, 5.23)). No effects were found for cerebrovascular causes. Conclusions We found evidence of strongest effects of particulate matter during Saharan dust days, providing a suggestion of effect modification, even though interaction terms were not statistically significant. Further investigation is needed to understand the mechanism by which Saharan dust increases mortality.